A comparison study of liquid and vapor phase development at spray boundary of diesel spray, BDF and SVO spray - Adam Mohd Izhan, Noor Azam (2012)
The use of biodiesel as an alternative diesel engine fuel is preferred for fossil fuel substitution. However, due to technical deficiencies, they are rarely used purely or with high percentages in unmodified diesel engines. Therefore, this project is to study spray simulation of diesel, biodiesel fuel (BDF) and straight vegetable oil (SVO) in the diesel chamber. Two main components are focused on this paper. First, the relations between the viscosities of different fuels and the spray characteristics in achieving stoichiometric air-fuel mixture are investigated. Lastly the spray liquid-vapor phase in chamber is investigated. Good spray characteristics lead to the good drivability, high combustion efficiency and stoichiometric air-fuel mixture. Therefore, Computational Fluid Dynamics (CFD) method using ANSYS Fluent simulation software is used for this purpose. The simulation of injection spray in chamber is conducted by using three type of fuel that is diesel, biodiesel and palm oil with the one 0.2mm valve covered orifice (VCO) nozzle, injection pressure at 700 MPA, ambient pressure at 10 MPA, ambient temperature at 300 K and same iteration time. The results are shown by changing the type of fuel. The simulation results showed that the spray characteristics are better for diesel at the same time iteration compared to BDF and SVO by the penetration length, cone angle and liquid-vapor phase data.